Modified boron nitride coordination platinum composite filler, preparation method and application thereof

CN122941065APending Publication Date: 2026-10-20FOSHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611036553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,该体系中铂催化剂以小分子形式直接分散于硅橡胶基体中,极易发生团聚而失活,且小分子改性剂在长期使用过程中易迁移析出,严重影响材料的长期稳定性和使用寿命

Benefits of technology

1.本发明利用3-氨丙基三乙氧基硅烷(AS)的氨基与铂之间的化学配位作用,将铂催化剂牢固锚定于BN载体表面。这种固载化有效限制铂的分子运动,有助于减少催化剂在加工和使用过程中的团聚与迁移,确保催化活性的长效性和稳定性。另外,Pt的催化作用与BN物理屏障的协同,材料在燃烧时能迅速形成连续、致密的无机层,有效抑制热量和可燃气体的传递,在耐漏电起痕阻燃硅橡胶复合材料的制备中,在较少的添加量情况下,依然能达到显著的耐漏电起痕与阻燃性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a modified boron nitride-coordinated platinum composite filler, its preparation method, and its applications, belonging to the field of composite material technology. This invention utilizes the chemical coordination between the amino group of 3-aminopropyltriethoxysilane (AS) and platinum to firmly anchor the platinum catalyst onto the BN support, effectively restricting the molecular motion of platinum, reducing aggregation and migration during processing and use, and ensuring the long-term effectiveness and stability of catalytic activity. Furthermore, the synergistic effect of Pt's catalytic activity and the physical barrier of BN allows the material to rapidly form a continuous and dense inorganic protective layer during combustion, effectively inhibiting the transfer of heat and combustible gases. In the preparation of tracking-resistant and flame-retardant silicone rubber composite materials, significant tracking resistance and flame retardant properties can still be achieved with relatively small amounts of Pt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite materials technology, and more specifically, to a modified boron nitride-coordinated platinum composite filler, its preparation method, and its application. Background Technology

[0002] Methyl vinyl silicone rubber (SR) is widely used as the sheathing material for high-voltage insulators due to its excellent electrical insulation, weather resistance, hydrophobicity, and resistance to high and low temperatures. However, during long-term outdoor operation, dirt inevitably accumulates on the insulator surface, which can easily lead to tracking and electrolytic corrosion damage in humid environments and under strong electric fields, potentially causing insulation failure or even power grid accidents. Furthermore, the insufficient flame retardancy of silicone rubber (its limiting oxygen index is typically only 20-25%) limits its application in higher voltage levels and harsher operating conditions.

[0003] Currently, a common method to improve the tracking resistance and flame retardancy of silicone rubber is to add a large amount of inorganic filler, such as aluminum hydroxide (ATH). However, the amount of ATH added is usually very large (up to 90-160 parts), which on the one hand will seriously dilute the silicone rubber segments, deteriorate the vulcanization performance and mechanical properties; on the other hand, ATH has poor compatibility with silicone rubber, and a large amount of filler will significantly reduce the processing performance and mechanical strength of the material. In addition, Chinese patent CN106009693A discloses a technical solution to improve the tracking resistance and thermal conductivity of silicone rubber by doping with two inorganic nanoparticles, ATH and BN. Although this solution utilizes the thermal conductivity of BN to alleviate local heat accumulation to some extent, it is essentially still a simple physical blending and fails to solve the key problems of BN's strong surface inertness and poor compatibility with the silicone rubber matrix. Moreover, the addition of a large amount of inorganic filler will still have an adverse effect on the mechanical properties.

[0004] In recent years, researchers have discovered that synergistic use of nitrogen-containing compounds with platinum catalysts can significantly improve the tracking resistance of silicone rubber at relatively low addition levels. For example, Chinese patent CN104974530A discloses a high-performance tracking-resistant silicone rubber, which achieves performance improvement by directly adding nitrogen-containing silanes and platinum compounds to the silicone rubber matrix. However, in this system, the platinum catalyst is directly dispersed in the silicone rubber matrix in the form of small molecules, which is prone to agglomeration and deactivation. Furthermore, the small molecule modifier is prone to migration and precipitation during long-term use, seriously affecting the long-term stability and service life of the material. In addition, simple physical mixing of platinum catalysts and nitrogen-containing compounds cannot maximize the synergistic effect, resulting in limited catalytic efficiency.

[0005] Based on this, the present invention provides a modified boron nitride-coordinated platinum composite filler, its preparation method, and its application, aiming to solve at least one of the problems in the prior art. Therefore, there is a need to develop or improve a modified boron nitride-coordinated platinum composite filler, its preparation method, and its application. Summary of the Invention

[0006] Based on this, in order to solve one of the above-mentioned technical problems, the present invention provides a modified boron nitride coordinated platinum composite filler, its preparation method, and its application. The specific technical solution is as follows: A modified boron nitride-coordinated platinum composite filler, wherein the modified boron nitride-coordinated platinum composite filler uses hexagonal boron nitride as a support, and the surface of the support is sequentially grafted with an organic modified layer formed by polysilazane and 3-aminopropyltriethoxysilane, and is anchored by the amino group in the 3-aminopropyltriethoxysilane and a platinum catalyst; wherein the polysilazane has a structural unit as shown in formula (I): -SiR1R2 NR3(Ⅰ); In formula (Ⅰ), R1, R2, and R3 are each independently selected from hydrogen, C1-C6 alkyl, and aryl.

[0007] Furthermore, the polysilazane is at least one of methylvinyl polysilazane and polyhydromethylsilazane; The platinum catalyst is a cassiterite catalyst.

[0008] In addition, the present invention also provides a method for preparing a modified boron nitride-coordinated platinum composite filler, the preparation method comprising the following steps: Step 1: Hydroxylation treatment: Disperse hexagonal boron nitride powder in deionized water, and then perform ultrasonic dispersion and crushing treatment in sequence to obtain a hydroxylated hexagonal boron nitride dispersion; Step 2: Grafting modification: Polysilazane and 3-aminopropyltriethoxysilane having the structural unit shown in formula (I) are added to the hydroxylated hexagonal boron nitride dispersion. After dispersion treatment, a reflux reaction is carried out under heating conditions. The product after reaction is filtered, washed and dried to obtain surface-modified hexagonal boron nitride. Step 3: Anchoring: The surface-modified hexagonal boron nitride is mixed with a platinum catalyst, so that the platinum interacts with the amino group in the 3-aminopropyltriethoxysilane, thereby anchoring the platinum to the surface of the surface-modified hexagonal boron nitride, and thus obtaining a modified boron nitride-coordinated platinum composite filler.

[0009] Furthermore, in step two, the mass ratio of polysilazane to 3-aminopropyltriethoxysilane is (0.1-2):1.

[0010] Furthermore, in step one, the mixture is ultrasonically dispersed at a temperature of 50-60℃ and a frequency of 100-200kHz for 1-3 hours, followed by a crushing treatment for 30-60 minutes.

[0011] Furthermore, in step two, the temperature of the condensation reflux reaction is 50-120℃, and the time is 1-24h.

[0012] In addition, the present invention also provides an application of the modified boron nitride coordinated platinum composite filler, wherein the application is the application of the modified boron nitride coordinated platinum composite filler in the preparation of tracking-resistant and flame-retardant silicone rubber composite materials.

[0013] Furthermore, the preparation of the tracking-resistant and flame-retardant silicone rubber composite material includes the following steps: Methyl vinyl silicone rubber raw rubber was placed on a two-roll mill for plasticizing; then the modified boron nitride coordinated platinum composite filler was added to the plasticized raw rubber and mixed evenly; then a vulcanizing agent was added and mixed evenly to obtain a compound rubber. The compound is subjected to a first-stage vulcanization molding and a second-stage vulcanization treatment to obtain a tracking-resistant and flame-retardant silicone rubber composite material.

[0014] Furthermore, the weight ratio of methyl vinyl silicone rubber raw rubber, modified boron nitride coordinated platinum composite filler, and vulcanizing agent is 100:(0.5-5.0):(1.0-3.0).

[0015] Furthermore, the temperature of the first-stage vulcanization molding is 150-180℃, the pressure is 5-15 MPa, and the time is 10-30 min; the temperature of the second-stage vulcanization treatment is 170-220℃, and the time is 2-6 h.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention utilizes the chemical coordination between the amino group of 3-aminopropyltriethoxysilane (AS) and platinum to firmly anchor the platinum catalyst onto the surface of a BN support. This immobilization effectively restricts the molecular motion of platinum, helping to reduce catalyst aggregation and migration during processing and use, ensuring long-term catalytic activity and stability. Furthermore, the synergistic effect of Pt's catalytic activity and the physical barrier of BN allows the material to rapidly form a continuous, dense inorganic layer during combustion, effectively suppressing the transfer of heat and combustible gases. In the preparation of tracking-resistant and flame-retardant silicone rubber composites, significant tracking resistance and flame retardant properties can still be achieved with relatively small amounts of Pt.

[0017] 2. This invention constructs a triple synergistic system of BN physical barrier, Pt catalytic crosslinking, and polysilazane / AS high-temperature in-situ conversion of inorganic protective layer. Under the action of electric arc high temperature, Pt catalyst induces silicone rubber to crosslink rather than degrade and crack, while polysilazane and AS are converted into dense Si-OCN / SiO2 inorganic layer. Combined with the physical barrier of heat and oxygen transfer of two-dimensional BN sheet, the three work synergistically to achieve significant resistance to tracking and flame retardancy.

[0018] 3. The preparation method of this invention employs conventional liquid-phase grafting and coordination reactions. The process parameters are within the range of conventional industrial production parameters, requiring no special high-pressure or high-temperature equipment. The operation is simple and the conditions are mild. Furthermore, the BN support is relatively inexpensive, and the grafting modification process is carried out in an aqueous phase or conventional solvent, making it easy to scale up production and possessing extremely high industrial transformation value. Attached Figure Description

[0019] The invention will be further understood from the following description taken in conjunction with the accompanying drawings. The components in the drawings are not necessarily drawn to scale, but rather the emphasis is on illustrating the principles of the embodiments. In different views, the same reference numerals designate corresponding parts.

[0020] Figure 1 This is a digital photograph of the sample after the tracking resistance test (4.5KV) of the silicone rubber composite material in Example 1. Figure 2 These are video screenshots of the flame retardant performance test results of the silicone rubber composite material in Example 1 during and after vertical combustion. Figure 3 A digital photograph of the silicone rubber material (SR) sample after the tracking resistance test (4.5KV) of Comparative Example 1. Figure 4 The video screenshots show the flame retardant performance test results of silicone rubber material (SR) for Comparative Example 1 during vertical combustion and after combustion. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0023] In one embodiment of the present invention, a modified boron nitride-coordinated platinum composite filler is provided, wherein the modified boron nitride-coordinated platinum composite filler uses hexagonal boron nitride as a support, and the surface of the support is sequentially grafted with an organic modified layer formed by polysilazane and 3-aminopropyltriethoxysilane, and is anchored by the amino group in the 3-aminopropyltriethoxysilane and the platinum catalyst; wherein the polysilazane has a structural unit as shown in formula (I): -SiR1R2 NR3(Ⅰ); In formula (Ⅰ), R1, R2, and R3 are each independently selected from hydrogen, C1-C6 alkyl, and aryl.

[0024] In one embodiment, the polysilazane is at least one of methylvinyl polysilazane and polyhydromethylsilazane; The platinum catalyst is a cassiterite catalyst.

[0025] In one embodiment, the present invention also provides a method for preparing a modified boron nitride-coordinated platinum composite filler, the method comprising the following steps: Step 1: Hydroxylation treatment: Disperse hexagonal boron nitride powder in deionized water, and then perform ultrasonic dispersion and crushing treatment in sequence to obtain a hydroxylated hexagonal boron nitride dispersion; Step 2: Grafting modification: Polysilazane and 3-aminopropyltriethoxysilane having the structural unit shown in formula (I) are added to the hydroxylated hexagonal boron nitride dispersion. After dispersion treatment, a reflux reaction is carried out under heating conditions. The product after reaction is filtered, washed and dried to obtain surface-modified hexagonal boron nitride. Step 3: Anchoring: The surface-modified hexagonal boron nitride is mixed with a platinum catalyst, so that the platinum interacts with the amino group in the 3-aminopropyltriethoxysilane, thereby anchoring the platinum to the surface of the surface-modified hexagonal boron nitride, and thus obtaining a modified boron nitride-coordinated platinum composite filler.

[0026] In one embodiment, the mass ratio of boron nitride to 3-aminopropyltriethoxysilane is (1-5):1.

[0027] In one embodiment, in step two, the mass ratio of polysilazane to 3-aminopropyltriethoxysilane is (0.1-2):1. Preferably, it is (0.5-2):1, more preferably (0.6-1.5):1.

[0028] In one embodiment, in step one, the mixture is ultrasonically dispersed at a temperature of 50-60°C and a frequency of 100-200kHz for 1-3 hours, followed by a crushing process for 30-60 minutes.

[0029] In one embodiment, in step two, the temperature of the condensation reflux reaction is 50-120°C, and the time is 1-24 hours.

[0030] In one embodiment, the preparation of the tracking-resistant and flame-retardant silicone rubber composite material includes the following steps: Methyl vinyl silicone rubber raw rubber was placed on a two-roll mill for plasticizing; then the modified boron nitride coordinated platinum composite filler was added to the plasticized raw rubber and mixed evenly; then a vulcanizing agent was added and mixed evenly to obtain a compound rubber. The compound is subjected to a first-stage vulcanization molding and a second-stage vulcanization treatment to obtain a tracking-resistant and flame-retardant silicone rubber composite material.

[0031] In one embodiment, the weight ratio of methyl vinyl silicone rubber raw rubber, modified boron nitride coordinated platinum composite filler, and vulcanizing agent is 100:(0.5-5.0):(1.0-3.0).

[0032] In one embodiment, the vulcanizing agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0033] In one embodiment, the temperature of the first-stage vulcanization molding is 150-180℃, the pressure is 5-15 MPa, and the time is 10-30 min; the temperature of the second-stage vulcanization treatment is 170-220℃, and the time is 2-6 h.

[0034] In the above scheme, through the triple synergistic mechanism of physical barrier of BN, platinum catalytic crosslinking and in-situ conversion of inorganic protective layer of polysilazane / AS, the silicone rubber composite material can achieve excellent resistance to tracking at a low addition amount. At the same time, the platinum catalyst is firmly anchored to the BN surface by the amino coordination effect, which effectively solves the industry problems of easy agglomeration and deactivation of platinum catalyst and easy migration of organic modifier in the prior art. The scheme achieves synergistic improvement of tracking resistance and flame retardant performance at extremely low filling amount, and the preparation process is mild and controllable, which has good prospects for industrial application.

[0035] The implementation schemes of the present invention will now be described in detail with reference to specific embodiments.

[0036] Example 1: The preparation of a tracking-resistant and flame-retardant silicone rubber composite material includes the following steps: 10.0 g of hexagonal boron nitride and 158 mL of deionized water were added to a beaker and dispersed using a 100 kHz ultrasonic cleaner at 55 °C for 9 h. The dispersion was then treated with a cell disruptor for 30 min to obtain a hydroxylated BN dispersion. 6 g of methylvinyl polysilazane and 8 g of 3-aminopropyltriethoxysilane (AS) were added dropwise to the hydroxylated BN dispersion. The mixture was further treated with a cell disruptor for 12 min, then transferred to a three-necked flask and mechanically stirred and refluxed in an 80 °C water bath for 6 h. After cooling, the reaction solution was filtered, and the solid was washed successively with ethanol and deionized water. After vacuum drying, the surface-modified hexagonal boron nitride was obtained. Surface-modified hexagonal boron nitride was mixed with a caster platinum catalyst (Pt loading was controlled so that the final Pt content in the rubber was 8 ppm), and the mixture was stirred thoroughly to allow the platinum and amino groups to fully combine, thus obtaining a modified boron nitride-coordinated platinum composite filler (gBN-Pt composite filler A). By weight, 100 parts of methyl vinyl silicone rubber raw rubber were plasticized on a two-roll mill, and 1.5 parts of modified boron nitride coordinated platinum composite filler (corresponding to a platinum content of about 8 ppm) were added. After uniform mixing, 1.5 parts of DBPMH were added and mixing continued. Then, the mixture was vulcanized at 165℃ and 10 MPa for 20 min, and then vulcanized in a second stage at 180℃ for 4 h to obtain a tracking-resistant and flame-retardant silicone rubber composite material.

[0037] The tracking-resistant and flame-retardant silicone rubber composite material prepared in Example 1 was subjected to performance testing. The test results were as follows: it passed the tracking resistance test (1A 4.5 level), the limiting oxygen index (LOI) was 29.0%, it achieved UL-94 V-1 rating in vertical burning, and the initial afterflame time was 21 seconds. Figure 1 and Figure 2 As shown.

[0038] Example 2: gBN-Pt composite filler A was prepared according to the method in Example 1; By weight, 100 parts of methyl vinyl silicone rubber raw rubber were plasticized on a two-roll mill, 1.3 parts of gBN-Pt composite filler A were added, and after uniform mixing, 1.5 parts of DBPMH were added and mixing continued. Then, it was vulcanized at 165℃ and 10 MPa for 20 min, and then vulcanized in a second stage at 180℃ for 4 h to obtain a tracking-resistant and flame-retardant silicone rubber composite material.

[0039] The tracking-resistant and flame-retardant silicone rubber composite material prepared in Example 2 was subjected to performance testing. The performance test results showed that the tracking resistance test was passed (1A 4.5 level). Its morphology after the tracking resistance test and the flame retardant test was similar to that of Example 1, and will not be described in detail here.

[0040] Example 3: Compared with Example 1, the Pt loading was controlled so that the Pt content in the final rubber was 12 ppm, and the rest was the same as in Example 1, thus preparing a tracking-resistant flame-retardant silicone rubber composite material.

[0041] The tracking-resistant and flame-retardant silicone rubber composite material prepared in Example 3 was subjected to performance testing. The performance test results showed that the tracking resistance test was passed (1A 4.5 level), and its morphology after the tracking resistance test and the flame retardant test was similar to that of Example 1.

[0042] Example 4: Compared with Example 1, Example 4 changed the ratio of methyl vinyl polysilazane and 3-aminopropyltriethoxysilane to 1:1, that is, (8g methyl vinyl polysilazane and 8g 3-aminopropyltriethoxysilane), while the rest was the same as Example 1.

[0043] The tracking-resistant and flame-retardant silicone rubber composite material prepared in Example 4 was subjected to performance testing. The performance test results showed that the tracking resistance test was passed (1A 4.5 level). Its morphology after the tracking resistance test and the flame retardant test was similar to that of Example 1, and will not be described in detail here.

[0044] Comparative Example 1: Pure Silicone Rubber (SR) No fillers were added, and the rest of the mixing and vulcanization process was the same as in Example 1.

[0045] The material in Comparison 1 will be subjected to performance tests. Performance: Tracking resistance fails (severe carbonization), LOI=25%, UL-94 NG, initial afterflame 38 s, etc. Figure 3 and Figure 4 As shown.

[0046] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the boron nitride added in Comparative Example 2 was not modified (i.e., 1.5 parts of boron nitride were used to replace the modified boron nitride-coordinated platinum composite filler), while the rest was the same as in Example 1.

[0047] The material prepared in Comparative Example 2 was subjected to performance tests. Performance: Tracking resistance failed, LOI=25%, UL-94NG, first afterflame 42 s. Its morphology after tracking resistance test and flame retardancy test was similar to that of Comparative Example 1.

[0048] Comparative Example 3: Compared to Example 1, in Comparative Example 3, 1.5 parts of surface-modified hexagonal boron nitride replaced the modified boron nitride-coordinated platinum composite filler (i.e., no platinum anchoring treatment was performed), and everything else was the same as in Example 1.

[0049] The material prepared in Comparative Example 3 was subjected to performance tests. Performance: Tracking resistance failed (some samples showed obvious carbonization channels), LOI=24%, UL-94 NG, first afterflame 35 s. Its morphology after tracking resistance test and flame retardancy test was similar to that of Comparative Example 1.

[0050] Figure 1 This is a digital photograph of the sample after the tracking resistance test (4.5KV) of the silicone rubber composite material in Example 1. From... Figure 1 As can be seen, there are no obvious electrolytic erosion channels or carbonization traces on the material surface. Given that it passed the 1A 4.5kV level test, it indicates that the Pt catalytic crosslinking and inorganic protective layer successfully suppressed the degradation and damage of the matrix by the electric arc, and no conductive carbon pathways were formed.

[0051] Figure 2 These are screenshots from a video showing the flame-retardant performance test of the silicone rubber composite material in Example 1, during and after vertical combustion. Figure 2As can be seen, the flame self-extinguished rapidly within 21 seconds after the first application, and the sample retained a relatively intact morphology after combustion. Since it meets the UL-94 V-1 standard, there should be no burning droplets igniting the absorbent cotton in the video, and the total afterflame time after both applications should not exceed 30 seconds. The screenshots visually demonstrate that the catalytic effect of Pt rapidly forms a dense inorganic layer on the surface, effectively blocking heat feedback.

[0052] Figure 3 This is a digital photograph of the silicone rubber material (SR) sample after the tracking resistance test (4.5KV) for Comparative Example 1. From... Figure 3 Analysis reveals that the tested rubber failed the test and was described as severely carbonized, even losing its insulating function. This indicates that the failure of pure silicone rubber under high-temperature electric arc conditions is due to pyrolysis rather than cross-linking.

[0053] Figure 4 The images shown are screenshots from a video during and after the vertical burning process of the flame-retardant performance test of the silicone rubber material (SR) in Comparative Example 1. Figure 4 As can be seen, the samples were severely deformed, disintegrated, or completely burned after combustion. Due to the UL-94 rating of NG (not compliant), the video shows molten flame droplets falling and igniting the degreased cotton at the bottom, and the total afterflame time far exceeds the standard limit, which clearly demonstrates the serious inadequacy of the flame retardant properties of pure silicone rubber.

[0054] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0055] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A modified boron nitride-coordinated platinum composite filler, characterized in that, The modified boron nitride-coordinated platinum composite filler uses hexagonal boron nitride as a support. The surface of the support is sequentially grafted with an organic modified layer formed by polysilazane and 3-aminopropyltriethoxysilane, and anchored by the amino group in the 3-aminopropyltriethoxysilane to the platinum catalyst. The polysilazane has structural units as shown in formula (I). -SiR1R2 NR3(Ⅰ); In formula (Ⅰ), R1, R2, and R3 are each independently selected from hydrogen, C1-C6 alkyl, and aryl.

2. The modified boron nitride-coordinated platinum composite filler according to claim 1, characterized in that, The polysilazane is at least one of methylvinyl polysilazane and polyhydromethylsilazane; The platinum catalyst is a cassiterite catalyst.

3. A method for preparing a modified boron nitride-coordinated platinum composite filler, characterized in that, The preparation method is used to prepare the modified boron nitride-coordinated platinum composite filler as described in claim 1 or 2, and the preparation method includes the following steps: Step 1: Hydroxylation treatment: Disperse hexagonal boron nitride powder in deionized water, and then perform ultrasonic dispersion and crushing treatment in sequence to obtain a hydroxylated hexagonal boron nitride dispersion; Step 2: Grafting modification: Polysilazane and 3-aminopropyltriethoxysilane having the structural unit shown in formula (I) are added to the hydroxylated hexagonal boron nitride dispersion. After dispersion treatment, a reflux reaction is carried out under heating conditions. The product after reaction is filtered, washed and dried to obtain surface-modified hexagonal boron nitride. Step 3: Anchoring: The surface-modified hexagonal boron nitride is mixed with a platinum catalyst, so that the platinum interacts with the amino group in the 3-aminopropyltriethoxysilane, thereby anchoring the platinum to the surface of the surface-modified hexagonal boron nitride, and thus obtaining a modified boron nitride-coordinated platinum composite filler.

4. The preparation method according to claim 3, characterized in that, In step two, the mass ratio of polysilazane to 3-aminopropyltriethoxysilane is (0.1-2):

1.

5. The preparation method according to claim 3, characterized in that, In step one, ultrasonic dispersion is performed at a temperature of 50-60℃ and a frequency of 100-200kHz for 1-3 hours, followed by crushing treatment for 30-60 minutes.

6. The preparation method according to claim 3, characterized in that, In step two, the temperature of the condensation reflux reaction is 50-120℃, and the time is 1-24h.

7. An application of a modified boron nitride-coordinated platinum composite filler, characterized in that, The application is the use of the modified boron nitride coordinated platinum composite filler as described in claim 1 or 2 in the preparation of tracking-resistant and flame-retardant silicone rubber composite materials.

8. The application according to claim 7, characterized in that, The preparation of the tracking-resistant and flame-retardant silicone rubber composite material includes the following steps: Methyl vinyl silicone rubber raw rubber was placed on a two-roll mill for plasticizing; then the modified boron nitride coordinated platinum composite filler was added to the plasticized raw rubber and mixed evenly; then a vulcanizing agent was added and mixed evenly to obtain a compound rubber. The compound is subjected to a first-stage vulcanization molding and a second-stage vulcanization treatment to obtain a tracking-resistant and flame-retardant silicone rubber composite material.

9. The application according to claim 8, characterized in that, The weight ratio of methyl vinyl silicone rubber raw rubber, modified boron nitride coordinated platinum composite filler, and vulcanizing agent is 100:(0.5-5.0):(1.0-3.0).

10. The application according to claim 8, characterized in that, The temperature of the first-stage vulcanization molding is 150-180℃, the pressure is 5-15 MPa, and the time is 10-30 min; the temperature of the second-stage vulcanization treatment is 170-220℃, and the time is 2-6 h.

Citation Information

Patent Citations

  • High-performance tracking-resistant silicone rubber and preparation method thereof

    CN104974530A

  • Silicone rubber with excellent tracking resistance and high heat conductivity

    CN106009693A